Sex Estimation using Footprint Ridge Density – A Mini Review - Seal, Saumya; Soták, Michal; Chovancová, Mária; Švábova, Petra; Beňuš, Radoslav (Anthropological Review, 2026)
INTRODUCTION The epidermal level of human footprint possesses raised ridges and furrows, which form unique patterns. Ridge density quantification, involving counting the ridges within a predefined unit area, emphasizes variability due to differences in epidermal ridge thickness. Analyses of these ridges exhibit sex-based differences, making it important for forensic identification purposes. STUDY AIM The present mini review was conducted to showcase a targeted synthesis of seven research articles related to sex estimation using Footprint Ridge Density (FPRD). METHODS Relevant studies were identified through the search engines Google Scholar, PubMed, Scopus and ResearchGate, using Boolean operators and/or, between 2010 and August 2025. RESULTS Higher FPRD were observed in females and statistically significant sexual dimorphism was inferred across plantar and toe regions, particularly at the medial ball and selected toe areas. CONCLUSIONS This review provides key inferences from the existing literature and points out the potentiality of using FPRD as a reliable parameter in sex estimation studies to improve forensic procedures.